Relationship between Procrastination and Academic Performance, Gender, Internal Housing among A Group of Undergraduate Dental Students in Misan-Iraq - Ousama Ibrahim; Mustafa M. Al-Yassiry; Farah K. Aloraibi (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study focuses on exploring the relationship between the academic procrastination and academicachievements for this study a survey was conducted on 132 students from first, fourth and fifth yearundergraduate dental students of Missan (government) & Almanara (private) universities, in Missan province-Alamara/Iraq. The present study investigate their academic procrastination and base it on various factorssuch as: gender, accommodation type, academic performance, procrastinator type, and year of study utilizingfrom Tuckman procrastination scale1, the study results were split into two parts. For Al-Manara collegeuniversity (private) first year dental students was the dominant high procrastinators student type associatedwith the low levels of academic performance and getting better grades when the procrastination stage ismoderate or low. While the Missan University (government) present the greatest of moderate procrastinatorin two different study stages of dental college (first, fourth and fifth year) coupled with significantly higherin the academic scores for low and moderate procrastinator students2.